Fouling deposit analysis of heat-induced pink guava puree - Chan, Ken Wei (2012)
Fouling deposit phenomena are common in industrial heat exchangers. It can accumulate during heat treatment and cooling process. The objectives of this work were to investigate the characteristics of pink guava puree (PGP) fouling deposit and to predict the effect of fouling deposit on tubular heat exchanger. The similarities of fresh and commercial PGP were investigated prior to fouling study. The properties (pH, total soluble solid, thermal conductivity, specific heat capacity, composition and rheology) of both purees were compared to determine the suitability of the commercial PGP as PGP fouling fluid model. Most properties of both purees behave similarly except for pH, total soluble solid (TSS) and rheology properties. There is a significant different for the pH and TSS for both puree (P<0.01). However, this may not affect the fouling rate significantly as the puree is carbohydrate based deposit. The rheology properties of both PGP showed significant difference only at low temperature, which will not affect the fouling study for heat induced deposit. The findings confirmed the suitability of commercial PGP for PGP fouling studies. In this work, pasteurization process is applied to obtain heat induced PGP fouling deposit. Heat transfer analysis of the heat exchanger during the pasteurization process was carried out. The PGP has accumulated to form fouling deposit and reduced heat transfer efficiency by 10.76% or 8.4661 W/m2°C during 360 minutes pasteurization process and the fouling deposit thickness in tube 4 was 2.4 mm in heating tube 4. The fouling deposit is classified as a carbohydrate-based deposit because it contains 28.5% of carbohydrate content. The fouling deposit has irregular structure that causes further fouling adhesion. The hardness increased by 59 % while its stickiness increased by 49% after 360 minutes operating time. The prediction on the effect of the fouling deposit on the heat exchanger was carried out by using empirical model and COMSOL Multiphysics software. The empirical model which has a coefficient of determination of 0.9562 prove that is can be used to predict the heat transfer coefficient of heat transfer during pasteurization for 24 hours. COMSOL Multiphysics software was used to simulate the effect of fouling deposit thickness on the temperature of the PGP. The prediction result shows that the fouling deposit is increasing with time. The economical lost due to PGP fouling was calculated in terms of energy and the chemical solution used to performed cleaning-in-place (CIP). The PGP fouling was found to cause an energy lost of RM1599.41 and RM52378.69 yearly in chemical solution respectively.